2008
DOI: 10.1116/1.2884762
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from as grown and nitrogen incorporated tetrahedral amorphous carbon/silicon heterojunctions grown using a pulsed filtered cathodic vacuum arc technique

Abstract: This article reports the field emission measurements on as grown tetrahedral amorphous carbon ͑ta-C͒ and nitrogen incorporated tetrahedral amorphous carbon ͑ta-C: N͒ films grown using a pulsed filtered cathodic vacuum arc technique. The effect of varying thickness on field emission in the as grown ta-C films and the effect of varying nitrogen content in ta-C: N films have also been studied. The values of threshold field of emission ͑E turn on ͒ increase with decrease of thickness in the as grown ta-C films. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
(66 reference statements)
0
10
2
Order By: Relevance
“…58 These values are larger to those reported for similar material by Satyanaryana et al, 36 or for nitrogen-containing carbon films reported by Amaratunga and Silva, 48 Weber et al, 49 and Panwar et al 37 grown under different process conditions. A space-charge-induced band bending and hot-electron transport model was proposed by Amaratunga and Silva 48 to explain low electron field-emission from a-C:H:N thin films.…”
Section: Comparison Of Results Obtained With Those Existing In Litcontrasting
confidence: 53%
See 4 more Smart Citations
“…58 These values are larger to those reported for similar material by Satyanaryana et al, 36 or for nitrogen-containing carbon films reported by Amaratunga and Silva, 48 Weber et al, 49 and Panwar et al 37 grown under different process conditions. A space-charge-induced band bending and hot-electron transport model was proposed by Amaratunga and Silva 48 to explain low electron field-emission from a-C:H:N thin films.…”
Section: Comparison Of Results Obtained With Those Existing In Litcontrasting
confidence: 53%
“…They achieved current densities up to 0.6 mA/ cm 2 at an electric field of 5.8 V / m. However, the values of E turn-on obtained in these ta-C:N films deposited with different N contents in the present study are larger than the values of E turn-on obtained by Satyanarayana et al 36 in ta-C:N films deposited at 80-100 eV ion energy using the L-bend FCVA process. The values of current density obtained in these ta-C:N films are larger than the values of current density obtained by Satyanarayana et al 36 and Panwar et al, 37 grown by a pulsed FCVA technique with an L-bend magnetic filter. Figure 9 shows the three-dimensional AFM image of ta-C:N films deposited with 12.7 at.…”
Section: Field-emission Measurements Of Ta-c:n Films With Different Ncontrasting
confidence: 47%
See 3 more Smart Citations